What is the role of Ewingella americana in humans? A case report in a healthy 4-year-old girl - Esposito, Susanna (BMC Infect Dis, 2019)
BACKGROUND: Ewingella americana (Ea) is a Gram-negative, lactose-fermenting, oxidase-negative and catalase-positive bacterium that was first described in 1983 as a new genus and species in the family Enterobacteriaceae. It is not known whether Ea is a true pathogen or simply an opportunistic infectious agent, as most of the cases have been described in patients at risk. CASE PRESENTATION: A 4-year-old girl described here was hospitalized due to a productive cough over the previous 3 weeks and a fever > 38 °C associated with tachypnea over the previous 2 days. Her familial and personal medical histories were negative for relevant diseases, including respiratory infections. At admission, she was febrile (axillary temperature 39.2 °C) and had dyspnea with retractions, grunting and nasal flaring. A chest examination revealed fine crackling rales in the left upper field associated with bilateral wheezing. A chest X-ray revealed segmental consolidation of the lingula of the left lung. Laboratory tests revealed leukocytosis (15.,800 white blood cells/mm(3) with 50.3% neutrophils), a slight increase in serum C-reactive protein (11.9 mg/L) and normal procalcitonin values (< 0.12 ng/mL). A nasopharyngeal swab culture did not reveal viral or bacterial respiratory pathogens, including atypical bacteria. A blood culture revealed the presence of a Gram-negative, lactose-fermenting rod that was oxidase negative and catalase positive. The isolate was identified by means of the VITEK®2 identification system (bioMérieux, Firenze, Italy) as Ea. This identification was confirmed by sequencing the 16 s ribosomal deoxyribonucleic acid (rDNA). The pathogen was sensitive to aminoglycoside, fluoroquinolones, carbapenems, cefotaxime, and ceftazidime but was intermediate against sulfametoxazole/trimethoprim and resistant to amoxicillin-clavulanic acid, fosfomycin, and oxacillin. The child was immediately treated orally with amoxicillin-clavulanic acid and erythromycin. Based on the results of a blood culture and sensitivity tests, the amoxicillin-clavulanic acid medication was stopped after 3 days. Erythromycin was continued for a total of 10 days, and the child was discharged after 3 days in the hospital. Follow-up visit 1 month later did not reveal any respiratory problems. CONCLUSION: This case shows that Ea infections in healthy subjects are mild even in pediatric age, and the need for antibiotic therapy is debated. Cases occurring in subjects with underlying chronic disease can be significantly more complicated and require appropriate antibiotic therapy.